Hubungan Kualitas Pelayanan Kesehatan Dengan Kepuasan Pasien Rawat Jalan Di Puskesmas X Kabupaten Grobogan - Yuliana; Dwi Nur Siti Marchamah; Rani Tiara Desty (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to determine the relationship between health service quality and outpatient satisfaction. The research method used is quantitative research with a cross sectional design. Respondents were patients aged 18-50 years who came to Puskesmas X Grobogan Regency in March-April 2023, totaling 500 patients. The sampling technique used non-probability sampling with accidental sampling technique, namely 83 respondents. The results of the validity test using the product moment person test were declared valid with a calculated value > 0.361 and the results of the reliability test with Cronbach's alpha coefficient (C) were declared reliable with a calculated value > 0.600. The normality test using the Kolomogorov-Smirnov test shows that the data is not normally distributed with a significance <0.05, namely 0.000. The results of the study used the chi-square test with a confidence level of 95%, namely that there was a significant relationship between the variables reliability (p value = 0.000), empathy (p value = 0.002), tangibility (p value = 0.002) on outpatient satisfaction. And there is no significant relationship between the variables of fast response (p value = 0.280), guarantee (p value = 0.511) on outpatient satisfaction.